2001
DOI: 10.1523/jneurosci.21-19-07715.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Entire Trajectories of Single Olivocerebellar Axons in the Cerebellar Cortex and their Contribution to Cerebellar Compartmentalization

Abstract: The functional partitioning of the cerebellar cortex depends on the projection patterns of its afferent and efferent neurons. However, the entire morphology of individual projection neurons has been demonstrated in only a few classes of neurons in the vertebrate CNS. To investigate the contribution of the projection pattern of individual olivocerebellar axons to the cerebellar functional compartmentalization, we labeled individual olivocerebellar axons, which terminate in the cerebellar cortex as climbing fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
191
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(211 citation statements)
references
References 30 publications
18
191
2
Order By: Relevance
“…3D-G), as reported previously (Sugihara et al, 2001). Figure 3 shows typical examples of individual longitudinal bands extending in both the rostral and caudal cerebellar cortex.…”
Section: A Specific Pair Of Aldolase C Compartments In the Rostral Ansupporting
confidence: 79%
See 3 more Smart Citations
“…3D-G), as reported previously (Sugihara et al, 2001). Figure 3 shows typical examples of individual longitudinal bands extending in both the rostral and caudal cerebellar cortex.…”
Section: A Specific Pair Of Aldolase C Compartments In the Rostral Ansupporting
confidence: 79%
“…The longitudinal organization has been further elaborated by the demonstration of zones A-D (Voogd, 1967;Groenewegen and Voogd, 1977; and even much narrower "microzones" (Andersson and Oscarsson, 1978), which are based on topographic corticonuclear Purkinje cell projection and olivocortical climbing fiber projection. Recent analyses have shown that the axon of an inferior olivary neuron provides multiple climbing fibers to a single narrow longitudinal band-shaped area comparable in size to a cortical microzone and sends collaterals to a small area in the cerebellar nucleus (Sugihara et al, , 2001. In contrast, a single lateral reticular nucleus neuron branches to form multiple mossy fibers that project to several longitudinal band-shaped areas .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mature rats, each CF provides an exceptionally strong synaptic input onto a few PCs in the cerebellum (34,35). Glutamate released at this synapse rapidly elicits a large non-N-methyl-Daspartic acid (NMDA) receptor-mediated EPSC that is strongly inhibited by ionotropic GluR antagonists.…”
Section: Discussionmentioning
confidence: 99%